2020
DOI: 10.21203/rs.2.23464/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is a Differentiated Care Model needed for Patients with TB? A cohort analysis of risk factors contributing to unfavourable outcomes among TB patients in two states in south India.

Abstract: Background: TB is a preventable and treatable disease. Yet, successful treatment outcomes at desired levels are elusive in many national TB programs, including India. We aim to identify risk factors for unfavourable outcomes to TB treatment, in order to subsequently design a care model that would improve treatment outcomes among these at-risk patients. Methods: We conducted a cohort analysis among TB patients who had been recently initiated on treatment. The study was part of the internal program evaluation of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Studies have shown that among PLHIV with comorbidities, particularly TB, there were benefits to extending intervals between clinic visits and ART pick-ups from pharmacies, however, routine TB screening was still needed and risk assessment at treatment initiation to identify factors associated with poor clinical outcomes was recommended. 24 , 25 Assessment and eligibility criteria may hamper access to the CCMDD program for patients who potentially have the most to gain from adaptive services. Additionally, there is also opportunity to use differentiated care not just for ART delivery, but for providing additional TB prophylaxis and screening that support both TB and HIV control measures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that among PLHIV with comorbidities, particularly TB, there were benefits to extending intervals between clinic visits and ART pick-ups from pharmacies, however, routine TB screening was still needed and risk assessment at treatment initiation to identify factors associated with poor clinical outcomes was recommended. 24 , 25 Assessment and eligibility criteria may hamper access to the CCMDD program for patients who potentially have the most to gain from adaptive services. Additionally, there is also opportunity to use differentiated care not just for ART delivery, but for providing additional TB prophylaxis and screening that support both TB and HIV control measures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the situation gets worse as TB clinics often do not monitor DM blood markers through finger prick glucose testing or H1Abc blood levels, thereby not having the chance to detect uncontrolled DM in patients. 50 Given that it is known that DM comorbid condition is a risk factor for various negative TB outcomes, TB clinics should offer differentiated care for this type of patients, 51 , 52 as it is feasible to manage uncontrolled DM if detected early in TB treatment. All this highlights the importance of monitoring, educating, and counseling when dealing with medication adherence in TB-DM patients.…”
Section: Tuberculosis and Diabetes: Twin Epidemicsmentioning
confidence: 99%